Global attitudes in the management of acute appendicitis during COVID‐19 pandemic: ACIE Appy Study. Issue 6 (8th October 2020) - Ielpo, B; Podda, M; Pellino, G; Pata, F; Caruso, R; Gravante, G; Di Saverio, S; ,
Abstract : The COVID‐19 pandemic required reorganization of surgical services, affecting patients with common surgical diseases including acute appendicitis. No evidence is available on the topic. This study found global variation in screening policies, use of personal protective equipment and intraoperative directives. There has been increased adoption of non‐operative management and open appendicectomy. Hands off Abstract: Background: Surgical strategies are being adapted to face the COVID‐19 pandemic. Recommendations on the management of acute appendicitis have been based on expert opinion, but very little evidence is available. This study addressed that dearth with a snapshot of worldwide approaches to appendicitis. Methods: The Association of Italian Surgeons in Europe designed an online survey to assess the current attitude of surgeons globally regarding the management of patients with acute appendicitis during the pandemic. Questions were divided into baseline information, hospital organization and screening, personal protective equipment, management and surgical approach, and patient presentation before versus during the pandemic. Results: Of 744 answers, 709 (from 66 countries) were complete and were included in the analysis. Most hospitals were treating both patients with and those without COVID. There was variation in screening indications and modality used, with chest X‐ray plus molecular testing (PCR) being the commonest (19·8 per cent). Conservative management of complicated and uncomplicated appendicitis was used by 6·6 and 2·4 per cent respectively before, but 23·7 and 5·3 per cent, during the pandemic (both P < 0·001). One‐third changed their approach from laparoscopic to open surgery owing to the popular (but evidence‐lacking) advice from expert groups during the initial phase of the pandemic. No agreement on how to filter surgical smoke plume during laparoscopy was identified. There was an overall reduction in the number of patients admitted with appendicitis and one‐third felt that patients who did present had more severe appendicitis than they usually observe. Conclusion: Conservative management of mild appendicitis has been possible during the pandemic. The fact that some surgeons switched to open appendicectomy may reflect the poor guidelines that emanated in the early phase of SARS‐CoV‐2.